A Beneficial Bipolar Hemiarthroplasty on a Centenarian in One Developing Country - Komang Agung Irianto Suryaningrat, Komang (Indonesian Society of Internal Medicine, 2021)
Abstract Geriatric hip fractures are common; however, surgery on a 100-year-old patient is rare in Indonesia. We report arthroplasty in 100-year-old woman with right hip fracture and right Colles fracture; which benefits her a three year of active and qualified life. Despite her age, the patient was quite independent, active, and mobile beforehand. Hence a meticulous preoperative planning and post-operative rehabilitation were structured by a comprehensive medic and non-medic geriatric team. Cementless bipolar hemiarthroplasty was perfectly sufficient for the hip fracture under regional anesthesia while the Colles fracture was managed with a close reduction and plastering. Rehabilitation was started on Day-2 and continued weeks after discharge. The patient is still alive and well 3 years after the surgery. Surgery is beneficial for the 100-year-old patient; it is in the best interests of the patient's mobility and quality of life. Age alone should not limit a surgical decision as long as all comorbidities are controlled by a comprehensive medic and non-medic geriatric team.